The Person Phrasemics in the Ukrainian Argot - Редько, Євген Олександрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article deals with formation specifics of the person phrasemes in the Ukrainian Argot systems. We have defined the specifics applicable to sociolect phrasemics, as well as the significance of metaphorization in the process of Argot phraseme formation. The special attention was focused on the description of phraseological nomens and also on its typical realizators (clothes, typical actions, health or unhealth of a person). The structural specifics of formation of Argot phraseological units were analyzed. Two tendencies of this process such as phrasemization of formative word-combination and reduction of the bigger syntaxeme, so called differentiation of the opinion were indicated.